2018
DOI: 10.1002/jctb.5589
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of bacterial methane elimination using porous ceramsite as biocarrier

Abstract: BACKGROUNDMethane is a greenhouse gas (GHG) which contributes to climate change. Biofiltration with immobilized methane‐oxidizing bacteria (MOB) is a promising option to eliminate methane. In order to achieve high methane removal efficiency (RE), the appropriate carrier material with favorable characteristics to perform well in MOB immobilization and methane elimination, must be selected.RESULTSA MOB consortium was enriched from landfill soil and immobilized on porous materials to eliminate methane at high (∼2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The MOB used in this study was mixed strains and mainly included 53.53% of Methylophilus and 0.003% of Methylomonas. 5 The MG and MOB strains were cultured using blue−green11 (BG11) medium and nitrate mineral (NMS) medium, respectively. Also, the ND medium, respectively.…”
Section: Biogas Slurry Mg (Chlorella Vulgaris) and Mobmentioning
confidence: 99%
“…The MOB used in this study was mixed strains and mainly included 53.53% of Methylophilus and 0.003% of Methylomonas. 5 The MG and MOB strains were cultured using blue−green11 (BG11) medium and nitrate mineral (NMS) medium, respectively. Also, the ND medium, respectively.…”
Section: Biogas Slurry Mg (Chlorella Vulgaris) and Mobmentioning
confidence: 99%
“…The MOB consortium was enriched from the soil, which was harvested from Xiaojianxi Landfill in Qingdao, Shandong, China. The enrichment processes were in compliance with the reported methods, and the nitrate mineral salts (NMS) medium with pH of 6.8 was used to provide nutrient elements for MOB (Sun et al, 2018c). Before inoculation, the MOB consortium was cultivated under methane concentration of 20% (v/v) at 25 • C with continuous shaking of 140 rpm.…”
Section: Enrichment Processmentioning
confidence: 99%
“…In our previous study, the MOB consortium has been inoculated in ceramsite to eliminate methane in batch experiments. The results showed that the MOB cells incorporated with black and red ceramsite prepared from fly ash and clay, respectively, kept improved methane ECs, which were 54.4% and 64.4%, respectively, higher than that of the suspended MOB cells during disposing 1% (v/v) of methane (Sun et al, 2018c). In this study, to verify the superiority, availability and stability of ceramsite in biofiltration for methane elimination, three lab-scale biofilters packed with fly ash ceramsite (FAC), clay ceramsite (CC) and active carbon, respectively, as support materials were constructed.…”
Section: Introductionmentioning
confidence: 98%
“…methanol, ethanol) to greenhouse gases (GHGs) [e.g. methane (CH 4 )] . According to US EPA 2018 (United States Environmental Protection Agency, 2018), atmospheric methanol and ethanol emissions are considered as hazardous air pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…methane (CH 4 )]. 1,2 According to US EPA 2018 (United States Environmental Protection Agency, 2018), 3 atmospheric methanol and ethanol emissions are considered as hazardous air pollutants. Methanol is broadly used as an organic solvent in the dye, resin and adhesive industries, as a feedstock for petrochemicals and as an additive for wastewater treatment units at denitrification step.…”
Section: Introductionmentioning
confidence: 99%